2012
DOI: 10.1371/journal.pone.0039330
|View full text |Cite
|
Sign up to set email alerts
|

ALCAM Regulates Motility, Invasiveness, and Adherens Junction Formation in Uveal Melanoma Cells

Abstract: ALCAM, a member of the immunoglobulin superfamily, has been implicated in numerous developmental events and has been repeatedly identified as a marker for cancer metastasis. Previous studies addressing ALCAM’s role in cancer have, however, yielded conflicting results. Depending on the tumor cell type, ALCAM expression has been reported to be both positively and negatively correlated with cancer progression and metastasis in the literature. To better understand how ALCAM might regulate cancer cell behavior, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…Likewise, they demonstrated that ALCAM was highly expressed on the surface of prostate stem/ progenitor and cancer initiating cells (Jiao et al, 2012). In melanoma, pancreatic-and prostate cancers, up-regulation of ALCAM is associated with invasion and metastasis (Jannie et al, 2012;Fujiwara et al, 2014;Hansen et al, 2014). Our findings support these previous studies -ALCAM up-regulated both mRNA and protein levels when the CAA cell line was induced to invasive character.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, they demonstrated that ALCAM was highly expressed on the surface of prostate stem/ progenitor and cancer initiating cells (Jiao et al, 2012). In melanoma, pancreatic-and prostate cancers, up-regulation of ALCAM is associated with invasion and metastasis (Jannie et al, 2012;Fujiwara et al, 2014;Hansen et al, 2014). Our findings support these previous studies -ALCAM up-regulated both mRNA and protein levels when the CAA cell line was induced to invasive character.…”
Section: Discussionsupporting
confidence: 89%
“…The location and increasing the expression of ALCAM in CCA cell line may suggest its roles in cell migration and invasion as found in other cancers (breast and pancreatic cancer) (Davies and Jiang, 2010;Fujiwara et al, 2014). In melanoma, silencing ALCAM expression in high-ALCAM expressed cell line a showed reduction of cell motility and invasiveness (Jannie et al, 2012). Moreover, blocking ALCAM with single-chain antibody inhibited invasiveness of breast cancer (Wiiger et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Although we have no functional data on the role of Alcama in retinal regeneration, its distribution along the radial Müller glial processes, which guide migration of rod precursors in the uninjured, growing fish retina (Raymond and Rivlin, 1987), suggests that Alcama-dependent adhesive interactions may mediate migration of progenitors in the neurogenic clusters. Interestingly, mammalian ALCAM also colocalizes with VE-and N-cadherin at lateral membrane domains in endothelial cell junctions (Ofori-Acquah et al, 2008); it is a marker for metastasis in human tumor cells, recruits N-cadherin and β-catenin to adherens junctions, and promotes motility in uveal melanoma cell lines (Jannie et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, the fraction of ALCAM-positive lesions increases according to invasiveness (Clark level) and thickness (Breslow index) of the melanocytic tumor (8). It was shown that any interference with ALCAM function affects melanoma cell movement and invasion (9,10) and that ALCAM triggers MMP2 and MMP14 activity (11). However, it is still not known how ALCAM overexpression is induced in melanomas and how it coordinates metastasis formation.…”
Section: Introductionmentioning
confidence: 99%